The Balance of Fundamental Social and Economic Rights of the EU In Light of The Charter of Fundamental Rights - Kazimierz STRZYCZKOWSKI (Communications of International Proceedings, 2021)
This paper is an attempt to present the ongoing process of reorientation of the European Union’s objectives resulting from changes in its axiological bases, now founded on the assumption of equivalence between economic growth and maintenance of the social cohesion. The basic task of the article is to address the issue whether the economic and social goals set forth in the Treaty of Lisbon have an equal status from the point of view of legal instruments ensuring their implementation and coherence, in other words from the perspective cohesion of the social policy’s regulation and the sustainable economic growth achievement on the example of social and economic fundamental rights.
Keywords: internal market; social policy; fundamental rights; competition law